2022
DOI: 10.3389/fcell.2022.980219
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitters, neuropeptides and calcium in oocyte maturation and early development

Abstract: A primary reason behind the high level of complexity we embody as multicellular organisms is a highly complex intracellular and intercellular communication system. As a result, the activities of multiple cell types and tissues can be modulated resulting in a specific physiological function. One of the key players in this communication process is extracellular signaling molecules that can act in autocrine, paracrine, and endocrine fashion to regulate distinct physiological responses. Neurotransmitters and neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 135 publications
(146 reference statements)
0
7
0
2
Order By: Relevance
“…The series of Ca 2+ oscillations that are seen in OA that are attributed to be the function of the “sperm factor” is believed to be the direct result of Ca 2+ release via (IP 3 -mediated reactions [ 10 , 15 , 28 , 43 , 44 , 45 ], and PLCs are a class of enzymes well characterised to be involved in the catabolism of phosphatidylinositol 4,5-bisphosphate (PIP 2 ) into IP 3 and diacylglycerol (DAG) [ 28 , 46 , 47 , 48 ]. PLCs have 13 known isoforms that can be classified based on function and structure and they are PLC beta (β1–4), PLC delta (δ1,3 and 4), PLC epsilon (ε), PLC eta (η1–2), PLC gamma (γ1–2), and PLC zeta (ζ) [ 28 , 47 , 49 , 50 , 51 , 52 ].…”
Section: The Mammalian Sperm Factor: Phospholipase C Zetamentioning
confidence: 99%
See 1 more Smart Citation
“…The series of Ca 2+ oscillations that are seen in OA that are attributed to be the function of the “sperm factor” is believed to be the direct result of Ca 2+ release via (IP 3 -mediated reactions [ 10 , 15 , 28 , 43 , 44 , 45 ], and PLCs are a class of enzymes well characterised to be involved in the catabolism of phosphatidylinositol 4,5-bisphosphate (PIP 2 ) into IP 3 and diacylglycerol (DAG) [ 28 , 46 , 47 , 48 ]. PLCs have 13 known isoforms that can be classified based on function and structure and they are PLC beta (β1–4), PLC delta (δ1,3 and 4), PLC epsilon (ε), PLC eta (η1–2), PLC gamma (γ1–2), and PLC zeta (ζ) [ 28 , 47 , 49 , 50 , 51 , 52 ].…”
Section: The Mammalian Sperm Factor: Phospholipase C Zetamentioning
confidence: 99%
“…The Ca 2+ oscillation signals the start as a result of the disturbance of cytosolic Ca 2+ equilibrium. This disturbance occurs as a response to stimulatory signals that act on Ca 2+ receptors which are found either in the cytoplasmic membrane or ER (Ca 2 store) and will result in an increase in cytoplasmic Ca 2+ [ 15 ]. Coordinated calcium waves will be produced by internal Ca 2+ stores, where a sudden increase of Ca 2+ will induce more Ca 2+ release through a series of events as positive feedback [ 16 ], a process termed calcium-induced calcium release (CICR).…”
Section: Introductionmentioning
confidence: 99%
“…To this degree, the control of mRNA degradation/translation status is major regulatory step, maintained both spatially and temporally, with specific regulatory factors exerting a critical role during early embryogenesis. Thus, such factors may also serve as important potential targets for RNA-based therapies (knockdown/expression as appropriate) (Teixeira and Lehmann, 2019;Alhajeri et al, 2022;Zhang et al, 2022). Further to maternal factors, Yuan et al (2023) reported that the paternal genome also exerts a significant influence during maternal RNA degradation (MRD) and ZGA in human early embryos, and mused whether the infertility of some patients may be attributable to defects of paternal contributors of human ZGA.…”
Section: Embryogenic Targetsmentioning
confidence: 99%
“…Tryptophan is not only an essential aminoacid for chickens, mainly used for protein synthesis, but also has various metabolic functions in the brain, such as the precursor of serotonin and melatonin (El-Slamoney et al, 2010;Khattak and Helmbrecht, 2019). Serotonin plays an important role in oocyte maturation, embryonic development, laying behavior, and improving intracellular Ca levels (Khattak and Helmbrecht, 2019;Alhajeri et al, 2022).…”
Section: Introductionmentioning
confidence: 99%